Exploration of Teachers' Difficulties in Managing Mathematics Learning on Sumatra Island - Simanjuntak, Sinta Dameria; Fadilah, Nina; Sembiring, Ribka Kariani; Sitompul, Pardomuan (International Journal of Trends in Mathematics Education Research, 2024)
This research explores the difficulties faced by mathematics teachers in Sumatra Island in managing learning. Using a descriptive qualitative approach, the research involved 91 junior high school teachers through written interviews with 10 open-ended questions. The research results revealed several main difficulties: limited understanding of the independent curriculum, challenges in developing teaching modules, difficulties in determining learning objectives from cognitive-affective-psychomotor aspects, challenges in designing learning that facilitates social-economic-cultural-religious aspects, and obstacles in implementing teaching methods that meet students' needs. Nevertheless, teachers have demonstrated good abilities in time management, facilitating student collaboration, providing feedback, and conducting learning reflections.